Intron retention as an excellent marker for diagnosing depression and for discovering new potential pathways for drug intervention - Okada, Norihiro; Oshima, Kenshiro; Maruko, Akiko; Sekine, Mariko; Ito, Naoki; Wakasugi, Akino; Mori, Eiko; Odaguchi, Hiroshi; Kobayashi, Yoshinori (Frontiers in Psychiatry, 2024)
Background Peripheral inflammation is often associated with depressive disorders, and immunological biomarkers of depression remain a focus of investigation. Methods We performed RNA-seq analysis of RNA transcripts of human peripheral blood mononuclear cells from a case-control study including subjects with self-reported depression in the pre-symptomatic state of major depressive disorder and analyzed differentially expressed genes (DEGs) and the frequency of intron retention (IR) using rMATS. Results Among the statistically significant DEGs identified, the 651 upregulated DEGs were particularly enriched in the term “bacterial infection and phagocytosis”, whereas the 820 downregulated DEGs were enriched in the terms “antigen presentation” and “T-cell proliferation and maturation”. We also analyzed 158 genes for which the IR was increased (IncIR) and 211 genes for which the IR was decreased (DecIR) in the depressed subjects. Although the Gene Ontology terms associated with IncIR and DecIR were very similar to those of the up- and downregulated genes, respectively, IR genes appeared to be particularly enriched in genes with sensor functions, with a preponderance of the term “ciliary assembly and function”. The observation that IR genes specifically interact with innate immunity genes suggests that immune-related genes, as well as cilia-related genes, may be excellent markers of depression. Re-analysis of previously published RNA-seq data from patients with MDD showed that common IR genes, particularly our predicted immune- and cilia-related genes, are commonly detected in populations with different levels of depression, providing validity for using IR to detect depression. Conclusion Depression was found to be associated with activation of the innate immune response and relative inactivation of T-cell signaling. The DEGs we identified reflect physiological demands that are controlled at the transcriptional level, whereas the IR results reflect a more direct mechanism for monitoring protein homeostasis. Accordingly, an alteration in IR, namely IncIR or DecIR, is a stress response, and intron-retained transcripts are sensors of the physiological state of the cytoplasm. The results demonstrate the potential of relative IR as a biomarker for the immunological stratification of depressed patients and the utility of IR for the discovery of novel pathways involved in recovery from depression.